An updated PREDICT breast cancer prognostication and treatment benefit prediction model with independent validation - Candido Dos Reis, Francisco J.; Wishart, Gordon C.; Dicks, Ed M.; Greenberg, David; Rashbass, Jem; Schmidt, Marjanka K.; van den Broek, Alexandra J.; Ellis, Ian O.; Green, Andrew; Rakha, Emad; Maishman, Tom; Eccles, Diana M.; et al. (BioMed Central, 2017)
BACKGROUND